Managing Mental Health Problems Among Immigrant Women Attending Primary Health Care Services. Issue 1 (2nd January 2016) - Straiton, Melanie L.; Powell, Kathryn; Reneflot, Anne; Diaz, Esperanza
Abstract : Researchers in Norway explore treatment options in primary care for immigrant women with mental health problems compared with nonimmigrant women. Three national registers were linked together for 2008. Immigrant women from Sweden, Poland, the Philippines, Thailand, Pakistan, and Russia were selected for analysis and compared with Norwegian women. Using logistic regression, we investigated whether treatment type varied by country of origin. Rates of sickness leave and psychiatric referrals were similar across all groups. Conversational therapy and use of antidepressants and anxiolytics were lower among Filipina, Thai, Pakistani, and Russian women than among Norwegians. Using the broad term "immigrants" masks important differences in treatment and health service use. By closely examining mental health treatment differences by country of origin, gaps in service provision and treatment uptake may be identified and addressed with more success.